Geopolitics in the era of globalisation mapping an alternative global future - Kumar, Yogendra 1952- (Routledge, Taylor & Francis Group, 2021)
This book presents an alternative roadmap for a world characterised by geopolitical uncertainty. The surging expectations about a future world of democratic values and high economic growth, born out of superpower bonhomie at the end of the Cold War, did not lead to the promised outcomes. Instead we are faced with deeply destabilising challenges, like climate change, widespread state fragility, terrorism, arms race, disruptive newer technologies, global economic volatility, and ineffectiveness of multilateral institutions, old and new. The volume: surveys the intellectual discourse, the attempts to redesign the global institutions, and the geopolitical trends since the end of the Cold War for an understanding of the contemporary geopolitics; analyses the characteristics of the contemporary geopolitics, the seeming intractability of the global challenges, and the ongoing discourse about preventing their further deterioration; foregrounds the Gandhian praxis and IR theory for managing power transitions anchored in non-violent mobilisation of empowered masses, ensuring institutional resilience, and illustrates them through ongoing conflicts in Iraq and Afghanistan; outlines an approach, based on the Gandhian experience of managing political change, towards conflict, geopolitical uncertainties, and institutional ineffectiveness for securing a better future globally, including South Asia